2017
DOI: 10.1007/s00726-017-2492-4
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli aggravates endoplasmic reticulum stress and triggers CHOP-dependent apoptosis in weaned pigs

Abstract: Intestinal cells can sense the presence of pathogens and trigger many important signaling pathways to maintain tissue homeostasis and normal function. Escherichia coli and lipopolysaccharides (LPS) are the main pathogenic factors of intestinal disease in pigs. However, the roles of endoplasmic reticulum stress (ERS) and its mediated apoptosis in intestinal malfunction induced by E. coli or LPS remain unclear. In the present study, we aimed to evaluate whether ERS could be activated by E. coli fed to piglets an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The GRP78, the major ER-resident chaperone, is well known as a biomarker of ERs in the course of disease [19,20]. If sustained ERs persisted, inflammatory and apoptotic pathways are activated, including the induction of CHOP, PERK, caspase-3, caspase-12 and NF-κB [21][22][23]. It has been reported that overexpression of CHOP led to apoptosis after ERs and participated in ERs related diseases [24].…”
Section: Discussionmentioning
confidence: 99%
“…The GRP78, the major ER-resident chaperone, is well known as a biomarker of ERs in the course of disease [19,20]. If sustained ERs persisted, inflammatory and apoptotic pathways are activated, including the induction of CHOP, PERK, caspase-3, caspase-12 and NF-κB [21][22][23]. It has been reported that overexpression of CHOP led to apoptosis after ERs and participated in ERs related diseases [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of UPR, the endoplasmic reticulum activates various transcriptional programs to enhance its protein folding capacity and cellular stress associated with reduced endoplasmic reticulum when the adaptive warning effect is produced [35]. For a prolonged period, the endoplasmic reticulum mediates apoptosis by activating transcription factors such as the CCAAT/enhancer-binding protein (C/EBP) homologous protein (CHOP/GADD153), Caspase-12, and the JNKdependent pathway [36,37]. CHOP is a specific transcription factor of ERS, which can be induced by IRE1, ATF6, and eIF2α, and finally activates Caspase3 to induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“… 18 The C/EBPζ gene regulates endoplasmic reticulum stress-mediated apoptosis which has been found in many tissues of pigs. 19 - 24 But the expression pattern of C/EBP gene family in pigs’ tissues also has not been systematically analyzed.…”
Section: Introductionmentioning
confidence: 99%